Physiological characteristics of nationally competitive female road cyclists and demands of competition - Martin, D. T.; McLean, B.; Trewin, C.; Lee, H.; Victor, J.; Hahn, A. G. (Sports Medicine, 2001)
There are few published data describing female cyclists and the studies available are difficult to interpret because of the classification of athletes. In this review, cyclists are referred to as either internationally competitive (International Cycling Union world rankings provided when available) or nationally competitive. Based on the limited data available it appears that the age, height, body mass (BM) and body composition of women cyclists who have been selected to the US and Australian National Road Cycling Teams from 1980 to 2000 are fairly similar. Female cyclists who have become internationally competitive are generally between 21 to 28 years of age, 162 to 174 cm, 55.4 to 58.8 kg and 38 to 51 mm (sum of 7 skinfolds) corresponding to 7 to 12% body fat. The lower BM and percentage body fat are traits unique to the most competitive women. Internationally competitive women cyclists also possess a slightly superior ability to produce a high absolute power output for a fixed time period and a noticeably greater ability to produce power output relative to BM. In Women's World Cup races, successful women (top 20 places) spend more time >7.5 W/kg (11 +/- 2 vs 7 +/- 2%, p < 0.01) and less time <0.75 W/kg (24 +/- 4 vs 29 +/- 3%, p = 0.05) compared with non-top 20 placed riders. Additionally, cyclists in the top 20 produced higher average power (3.6 +/- 0.4 vs 3.1 +/- 0.1 W/kg, p = 0.01). Unlike professional men's road cycling, the physiological characteristics of internationally competitive female road cyclists and the demands of women's cycling competition are poorly understood.